PENGARUH LATIHAN CIRCUIT TRAINING TERHADAP DAYA TAHAN AEROBIK (VO2MAX) TIM BOLA VOLI PUTRA SMA NEGERI 2 KUOK - Putra, Aidhil Dwi; Sulastio, Agus; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:This study aims to determine the effect of circuit training on aerobic endurance (VO2 max) for the men's volley ball team at SMA Negeri 2 Kuok. This research was carried out in the Field of SMA Negeri 2 Kuok, carried out in March-August 2021. This study used one group, so this study used a one-group pretest-posttest design approach. The population in this study amounted to 12 people consisting of the male group. Sampling is determined by taking the entire population as a sample (total sampling). The instrument of this study used the 15-minute running Balke test. The analysis technique used t-test. Based on the t-test, the result is tcount of 2,381 with ttable of 1,796, it is rejected, at the alpha level (0. 05. It can be concluded that there is an effect of circuit training on the endurance of the men's volley ball team at SMA Negeri 2 Kuok. Key Words: Circuit Training, Vo2Max Endurance, Vollyball